2002
DOI: 10.1007/bf02982136
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 6 Meningoencephalitis Successfully Treated with Ganciclovir in a Patient Who Underwent Allogeneic Bone Marrow Transplantation from an HLA-Identical Sibling

Abstract: Human herpesvirus 6 (HHV-6) has recently been recognized as an important pathogen in immunocompromised hosts, such as patients who have undergone allogeneic bone marrow transplantation (allo-BMT). Here we report a case of HHV-6 meningoencephalitis in a patient who underwent allo-BMT from an HLA-identical sibling. The patient suffered from headache, high fever, tremor, and disorientation on day 35 after allo-BMT. Findings at magnetic resonance imaging, electroencephalography, and routine cerebrospinal fluid (CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Acyclovir [73,81] No No Ganciclovir [66][67][68][70][71][72] Yes Yes Mutation in U38 DNA polymerase Mutation in U69 phosphotransferase Foscarnet [65,[82][83][84][85] Yes Yes 2 Mutation in U38 DNA polymerase Cidofovir [76,86,95] Yes Yes Mutation in U38 DNA polymerase Maribavir [87,88] No Not available Cyclopropavir [89] Yes…”
Section: Mechanism Of Antiviral Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Acyclovir [73,81] No No Ganciclovir [66][67][68][70][71][72] Yes Yes Mutation in U38 DNA polymerase Mutation in U69 phosphotransferase Foscarnet [65,[82][83][84][85] Yes Yes 2 Mutation in U38 DNA polymerase Cidofovir [76,86,95] Yes Yes Mutation in U38 DNA polymerase Maribavir [87,88] No Not available Cyclopropavir [89] Yes…”
Section: Mechanism Of Antiviral Resistancementioning
confidence: 99%
“…In vitro studies demonstrated the activity of ganciclovir against HHV-6 [64,65] . Clinically, ganciclovir has been shown to be effective in HHV-6 infected bone marrow transplant recipients [66][67][68][69][70] . Likewise, case reports suggest that ganciclovir is effective for the treatment of HHV-6 infections after liver transplantation [66][67][68][70][71][72] .…”
Section: Mechanism Of Antiviral Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…In most reports, some antiviral activity is reported for ganciclovir although in certain cases of fulminant HHV6 infection showed no response. [44][45][46][47][48] Use of ganciclovir is complicated by severe bone marrow suppression which is an unwanted side-effect early after HSCT. 49 As in almost all patients suffering from HHV6 reactivation, prophylactic acyclovir was prescribed to prevent VZV/HSV reactivation, acyclovir appears to be ineffective against HHV6.…”
Section: Prevention and Therapy Of Hhv6 Reactivationmentioning
confidence: 99%
“…While ganciclovir appears to have a role in prophylaxis [39], preemptive therapy [40], and curative treatment [41], there are reports of patients developing HHV-6-induced encephalitis while on ganciclovir. There are several in vitro reports of ganciclovir resistance to HHV-6A strains [42].…”
Section: Discussionmentioning
confidence: 99%